MODEL PENGELOLAAN SAMPAH RUMAH TANGGA DI DESA TEGAL KERTHA KECAMATAN DENPASAR BARAT KOTA DENPASAR - Artayasa, I Nyoman; Pariartha, I Wayan Wana; Wiasta, I Wayan (Alam Lestari, 2012)
Production of household waste per day are increasing with the increase of population and consumption patterns. Things to be done to solve the increase in the volume of waste is by problem: reducing the volume of waste from its source through waste segregation.Model studies on waste management in the village of Tegal Kertha Denpasar Barat, Denpasar city aims to gain an description of Household Waste Management Model. This research type is qualitative descriptive, which describe phenomena that occur location research. Data collection techniques include interviews, questionnaires, and documentation, while the data analysis using qualitative descriptive techniques.The study concludes that the Household Waste Management Model in the village of Tegal Kertha is forming a group self-management of waste transport is coordinated directly by the Government of Tegal Kertha village. Waste transported and disposed of in the garbage cart TPS/Depo-Maning Monang. Waste brought to the TPS divided between the organic waste and an organic waste. An organic waste is collected according to its kind and sold to scrap collectors. While organic waste disposed of without being processed first.Household waste management model in the village of Tegal Kertha covers several aspects such as the operational technical aspects, institutional aspects, legal and regulatory aspects, financial aspects and aspects of community participation. Suggestions based on research results that this model is more effective and efficient it is expected that all families in the village of Tegal Kertha come into the garbage and in the future customers in order to process organic waste into compost. An organic waste process into items more valuable economically.